2021
DOI: 10.3847/psj/abf928
|View full text |Cite
|
Sign up to set email alerts
|

Collisional Evolution of the Inner Zodiacal Cloud

Abstract: The zodiacal cloud is one of the largest structures in the solar system and strongly governed by meteoroid collisions near the Sun. Collisional erosion occurs throughout the zodiacal cloud, yet it is historically difficult to directly measure and has never been observed for discrete meteoroid streams. After six orbits with Parker Solar Probe (PSP), its dust impact rates are consistent with at least three distinct populations: bound zodiacal dust grains on elliptic orbits (α-meteoroids), unbound β-meteoroids o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 76 publications
6
45
0
Order By: Relevance
“…Previous studies (Malaspina et al, 2020;Pusack et al, 2021;Szalay et al, 2020Szalay et al, , 2021 have shown that the dust count rate varies considerably with the distance to the Sun, but also the relative motion and orientation of the spacecraft. This rate is highest during the encounter phase.…”
Section: Example: Magnetic Signature Of Dust Impactsmentioning
confidence: 99%
“…Previous studies (Malaspina et al, 2020;Pusack et al, 2021;Szalay et al, 2020Szalay et al, , 2021 have shown that the dust count rate varies considerably with the distance to the Sun, but also the relative motion and orientation of the spacecraft. This rate is highest during the encounter phase.…”
Section: Example: Magnetic Signature Of Dust Impactsmentioning
confidence: 99%
“…In other PSP-based dust studies, Szalay et al (2021) recently showed that the trajectory of PSP around its perihelion is passing through regions of variable dust density. In addition to the orbiting zodiacal dust particles, there are some regions of increased dust density, as for example, in the trails of short-period comets or asteroids (e.g., Stenborg et al 2018b;Battams et al 2020, and references therein), or in circumsolar rings nearby the orbits of Venus (Leinert & Moster 2007;Jones et al 2013Jones et al , 2017Stenborg et al 2021a) or Earth (e.g., Reach et al 1995).…”
Section: Introductionmentioning
confidence: 98%
“…This would also explain the existence of gaps in the first 180 days after 2013 January 1, when on certain days Jorgensen et al (2021) reports 100+ STEs per day (i.e., total of 1000+ impacts per day considering 7% STE detection efficiency), while on subsequent days there are no impacts recorded at all. This kind of behavior does not follow the expected Poisson statistics seen for other meteoroid-related phenomena, such as impacts on other spacecraft (e.g., Page et al 2020;Pusack et al 2021;Szalay et al 2021), meteor detections at Earth (e.g., Pokorný & Brown 2016;Jenniskens et al 2020), or responses of airless bodies to meteoroid impacts (e.g., Burger et al 2014;Szalay & Horányi 2015). For an overview of the observations and modeling of meteoroid-related phenomena, see the recent review work by Janches et al (2021).…”
Section: Discussionmentioning
confidence: 88%
“…In fact, there are almost no STEs between the G1 and G2 data gaps, where Juno's R hel reaches its minimum below 1 au. From a multitude of in-situ spacecraft data, we know there should be a considerable meteoroid flux of bound grains at and below 1 au (e.g., Gruen et al 1980;Szalay et al 2021), and we would not expect the zodiacal cloud to exhibit increasing density with increasing heliocentric distance. What causes the discord between the observation and the model?…”
Section: Results: Meteoroid Model Impacts On Juno Solar Arraysmentioning
confidence: 99%